Pengaruh Employer Branding dan Budaya Organisasi terhadap Minat Melamar Kerja pada Gen Z di Wilayah Cileungsi - Haq, Gibran Ziyadul; Hasanah, Hasanah (Economic Reviews Journal, 2026)
The growing dominance of Generation Z within today’s labor market has encouraged organizations to re-evaluate their recruitment approaches, with greater attention directed toward Employer Branding and the articulation of organizational values. This research examines how Employer Branding and organizational culture contribute to shaping Generation Z’s interest in applying for employment opportunities in the Cileungsi region. A quantitative associative method was employed, with data collected through questionnaires distributed to 90 Generation Z respondents. The results demonstrate that Employer Branding exerts a positive and statistically significant effect on job application interest (t = 4.799; sig = 0.001 < 0.05), whereas organizational culture does not show a significant partial influence (t = 1.263; sig = 0.210 > 0.05). Nevertheless, when assessed simultaneously, Employer Branding and organizational culture jointly have a significant impact on job application interest (F = 35.179; sig = 0.001 < 0.05). The coefficient of determination (R² = 0.447) indicates that both variables account for 44.7% of the variance in Generation Z’s job application interest. Overall, these findings suggest that Employer Branding serves as the primary driver in attracting Generation Z job applicants, while organizational culture appears to be less influential during the initial stage of recruitment.